1986
DOI: 10.3928/1081-597x-19860101-05
|View full text |Cite
|
Sign up to set email alerts
|

Planar Lamellar Refractive Keratoplasty

Abstract: Satisfactory clinical results have been obtained with lamellar refractive keratoplasty (keratophakia, keratomileusis, and epikeratophakia). However, the techniques are accompanied by several disadvantages, most notably technical difficulty, inaccuracy, delayed visual rehabilitation, and excessive tissue destruction due to freezing or lyophilization. The author herein describes a new technique that is capable of producing lamellar refractive lenticules without the use of freezing or lyophilization, thereby main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Instead of freezing the resectioned cornea, the corneal cap was placed on a suction mould based on the attempted refractive correction for the microkeratome to make the refractive cut. Unfortunately, it too was unsuccessful at correcting astigmatism but on the plus side, it was associated with fewer complications than freeze techniques …”
Section: Keratomileusismentioning
confidence: 99%
“…Instead of freezing the resectioned cornea, the corneal cap was placed on a suction mould based on the attempted refractive correction for the microkeratome to make the refractive cut. Unfortunately, it too was unsuccessful at correcting astigmatism but on the plus side, it was associated with fewer complications than freeze techniques …”
Section: Keratomileusismentioning
confidence: 99%
“…10,11 This BKS non-freeze technique involved placing the ressected disc epithelial side down onto a curved suction die or mold where a second pass of the microkeratome removed tissue from the exposed posterior stromal surface according to the shape of the die (Fig 6). 10,11 This BKS non-freeze technique involved placing the ressected disc epithelial side down onto a curved suction die or mold where a second pass of the microkeratome removed tissue from the exposed posterior stromal surface according to the shape of the die (Fig 6).…”
Section: Barraquer-krumeich-swinger Techniquementioning
confidence: 99%
“…Keratomileusis in situ (Figure 6) consists of removing two concentric, lamellar disks from the anterior cornea, the second underlying resection being smaller in diameter than the first. [34][35][36][37] The devices that remove these lamellar tissues are known as microkeratomes. The first disk contains the epithelium, Bowman's membrane, and some anterior stroma, and is left attached to the stroma by a hinge as discussed earlier.…”
Section: Keratomileusis In Situmentioning
confidence: 99%
“…Similarly, it may be shown that a 10-D corrective cut at 5.5 mm will have an insert radius of 37.6 mm, a central tissue thickness of 100.70 m, a 5.4-mm optical zone, and a resultant power reduction of 9.7 D. It may be analytically shown that the preoperative anterior corneal radius R O does not significantly affect the insert radius R I required to correct for a known refractive error. 4,34,43 Therefore the optical inserts only need to be specified in terms of optical power and not as a function of preoperative corneal radius.…”
Section: Optical Verificationmentioning
confidence: 99%